Space Reduction using String and Synonym Matching Algorithm (SSMA) - Ghosh, Papri; Chingtham, Tejbanta Singh; Ghose, Mrinal Kanti (International Journal of Computer Sciences and Engineering, 2025)
The Command Based System (CBS) is one of the fields of Human Computer Interaction (HCI). In the modern era the Command Based System is enormously explored by many scientists and it is used in many fields. This study proposes to develop a new approach to build up a Command Based System which will accept a Text as an input and take the corresponding action. In this paper the String and Synonym Matching Algorithm (SSMA) is made to develop a String Command Based System (SCBS). The String and Synonym Matching Algorithm (SSMA) Algorithm focuses on the comparison between the users given string with the preloaded strings in the system database. The comparison is made in two ways i.e. a straight string comparison and the comparison between all the synonyms of the input string with the preloaded strings from the system database. The trick of matching the synonyms of the user given string reduces the space in the system database and increases the flexibility of the user to give more input with same meaning.